Conservation awareness, interpretation, and presentation of a heterotopic space and heritage site the case of Manila North Cemetery - Pascual , Jerome G.; Lico, Gerard Rey A. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The level of awareness raised for conserving historical structures and spaces such as houses, churches, and monumental edifices sparked a beautiful cause for Philippine Heritage. Together with various efforts to solidify this cause, appropriations and institutions worked hand in hand. But still, as the cause and implementation of heritage conservation widens, its coverage and comprehensibility must also be intensified. We associate sementeryo, pantyons, and campo santos with so much mourning and grief since all of us have at least a dead loved one interned in one of these memorial sites. ?We trudge through life knowing that these loved ones were already silenced and the graves they\re in denotes a sense of finality. One of the main purposes of heritage conservation is to ensure that historical structures and spaces remain for appreciation and use of present to future societies. We've seen and learned about a wide breadth of places of worships and local abodes restored but we haven't much encountered places of the dead given equal attention. According to the mirror analogy of Foucault, sites and spaces can be highly heterotopic, acting as mirrors to life - reflecting the real, and with this reflection of reality too hard to contain, people acted with evasive tendencies towards this reflection. Such is the facet of death found in hererotopias like the cemetery, a mirror reflecting both presence and absence. In his further discussion of the cemetery as heterotopic space, Foucault raised the alarming shift of modern society from giving importance to cemeteries containing history and heritage towards putting it to total alienation. The primary goal of the study is to impress the notion that the architectural conservation of our local cemeteries equates to the conservation of a Filipino space - complete with its crises, grievances, elements, and dynamics. That in assessing a heritage site like a cemetery, its significance and spirit of place can be better affected and embodied by a heritage interpretation and awareness assessment. With the present conservation practice of establishing a heritage site's cultural significance thru any prevailing architectural, social, historical, or spiritual criterion, a more comprehensive understanding of the cemetery can be encapsulated; furthering a more holistic perception of documenting and conserving cemeteries. This is done through Manila North Cemetry as a case study. The general objective of the study is to effectively and holistically establish a possibly cultural significance for a Filipino cemetery such as the Manila North Cemetery. The cemetery being an architectural feat in its primary nature of emplacing a "placeless" deceased society as inactive and immobile general end-users, dynamically amalgamates with the living and together form a unique heterotopic heritage site. Also, once its distinct heterotopian cultural significance is distilled, proposal to raise heritage awareness would be envisioned using ICOMOS Charter for the interpretation and presentation of cultural heritage sites.
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: Cemeteries; Historic sites; Historic sites -- Conservation and restoration